Space-Focused Stereotypes About People Living With HIV/AIDS and the Effects on Community-Approaching Willingness - Wen, Fangfang; Wang, Yang; Zuo, Bin; Yang, Jian; Qiao, Yalan; Ye, Hanxue; Luo, Zengqi (Frontiers in Psychology, 2022)
Targeting people living with Human Immunodeficiency Virus (HIV), this research examined the prevalence of space-focused stereotypes and their underlying mechanism on behavioral inclinations. Study 1 adopted the explicit nomination and implicit Go/No-Go association tests to explore the existence of space-focused stereotypes of people living with HIV/AIDS. The results demonstrated that space-focused stereotypes were only manifested explicitly, with characteristics such as messy, dirty, and gloomy. Study 2 demonstrated a more negative evaluation and community-approaching willingness for communities where people living with HIV/AIDS than those without HIV/AIDS. Additionally, the influence of space-focused stereotypes on community-approaching willingness was indirect, which was mediated by both emotional (threat perception) and cognitive factors (community evaluation). These results indicate the deviation of explicit and implicit space-focused stereotypes. More importantly, it revealed that space-focused stereotypes decreased community evaluation and influenced behavioral inclination. This research suggested the existence of space-focused stereotypes on another stigmatized social. Characteristics of space (e.g., geographical segregation) might be the key to forming space-focused stereotypes.